The partial skeleton StW 431 from Sterkfontein - Is it time to rethink the Pio-Pleistocene Hominin diversity in South Africa ? - (:unkn) unknown (My University, 2020)
The discovery of the nearly complete Plio-Pleistocene skeleton StW 573 Australopithecus prometheus from Sterkfontein Member 2, South Africa, has intensified debates as to whether Sterkfontein Member 4 contains a hominin species other than Australopithecus africanus. For example, it has recently been suggested that the partial skeleton StW 431 should be removed from the A. africanus hypodigm and be placed into A. prometheus. Here we re-evaluate this latter proposition, using published information and new comparative data. Although both StW 573 and StW 431 are apparently comparable in their arboreal (i.e., climbing) and bipedal adaptations, they also show significant morphological differences. Surprisingly, StW 431 cannot be unequivocally aligned with either StW 573 or other hominins from Sterkfontein commonly attributed to A. africanus (nor with Paranthropus robustus and Australopithecus sediba). This finding, together with considerations about the recent dating of Plio-Pleistocene hominin-bearing sites in South Africa and palaeoecological/palaeoclimatic conditions, raises questions whether it is justified to subsume hominins from Taung, Makapansgat and Sterkfontein (and Gladysvale) within a single taxon. Given the wealth of fossil material and analytical techniques now available, we call for a re-evaluation of the taxonomy of South African Plio-Pleistocene hominins. Such an endeavour should however go beyond the current (narrow) focus on establishing an A. africanus-A. prometheus dichotomy.
Keywords: African Research